DETERMINATION AND CONTROL OF WELDING VOLTAGES - Madaliyev Samandar Dilshod o’g’li; Abdukarimova Ferishtabonu Azimjonovna; Fazilov Dusmurat Saydivaliyevich (Western European Studies, 2024)
The purpose of this paper is to analyze methods for determining and strategies for controlling stresses in weld zones. We will review the physical principles underlying the formation of stresses, methods for their measurement, and innovative approaches to prevent and manage these stresses. Welding stresses arise from a number of factors including thermal effects, expansion and contraction of materials, and changes in metal structure. Stress measurement techniques include the use of strain gages, deformation methods, and advanced stress visualization techniques
Keywords: stress control; welding process optimization; treatment mechanical properties of materials